2015
DOI: 10.1111/jpc.13011
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial characteristics and predictors of health‐care use in families of young children with cystic fibrosis in Western Australia

Abstract: Social gradients may exist for families of young children with cystic fibrosis in Western Australia with potential implications for child health. Family psychological and relationship stress predicted increased child cystic fibrosis-related health-care use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 15 publications
2
12
0
Order By: Relevance
“…Mothers of CF patients who had frequent hospital visits or frequent hospitalizations were more overprotective, rejected the housewife role and had marital conflicts. Similar to a study conducted by Douglas et al ., 15 parental separation and marital disharmony were frequently observed in families of children with CF , and increased hospital and emergency visits could be predicted in these families. Furthermore, as increased hospitalizations were associated with more strict and authoritarian behaviour, it is obvious that CF affects the whole family negatively, although its influence on mothers is most prominent 2,16 .…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…Mothers of CF patients who had frequent hospital visits or frequent hospitalizations were more overprotective, rejected the housewife role and had marital conflicts. Similar to a study conducted by Douglas et al ., 15 parental separation and marital disharmony were frequently observed in families of children with CF , and increased hospital and emergency visits could be predicted in these families. Furthermore, as increased hospitalizations were associated with more strict and authoritarian behaviour, it is obvious that CF affects the whole family negatively, although its influence on mothers is most prominent 2,16 .…”
Section: Discussionsupporting
confidence: 82%
“…It can be considered that concern for the future, worsening disease outcomes, frequent hospital visits, and frequent hospitalizations keep mothers away from their family and social circle, resulting in depression and affecting their attitude towards child-rearing. Moreover, Douglas et al 15 showed that marital conflict, as well as maternal and child psychological stress, strongly predicted increased hospital admissions and emergency and outpatient visits, which can cause a vicious cycle to emerge in CF families. This study's findings reveal that CF severity affects marital conflict.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It further demonstrated that lower maternal education attainment was associated with having fewer exacerbations treated with home IV antibiotics, despite the number of stable visits being consistent across groups 19 . In a study of pediatric patients performed in Western Australia, marital discord and family psychological distress were significant predictors of increased hospitalizations, emergency, and outpatient visits in early life CF after adjusting for disease severity 22 . In a population of pediatric patients with noncomplex chronic conditions, it was found that having social complexity risk factors were significantly associated with the need for care coordination 23 .…”
Section: Discussionmentioning
confidence: 99%